Pendampingan Tahsin dan Tadabbur Al-Qur’an melalui QS. Luqman Ayat (12–19) pada Mahasiswa PAI Semester IV - Suriyati Suriyati; Suriati Suriati; Jamaluddin Jamaluddin; Rahmatullah Rahmatullah; Aulia Ananda; Kurniawati Kurniawati (PENDIMAS: Jurnal Pengabdian Masyarakat, 2026)
This Community Service Program (PKM) was initiated due to the fact that some students of the Islamic Education Study Program (PAI) were not yet optimal in reciting the Qur’an in accordance with the rules of tajwid and had limited understanding of the educational values contained within it. Therefore, this program aimed to improve the students’ tahsin (Qur’anic recitation improvement) skills and their understanding of tadabbur (Qur’anic reflection) through mentoring on Surah Luqman verses 12–19. The method applied was participatory mentoring conducted in three stages: preparation, implementation, and evaluation, using observation, and documentation as data collection techniques. The results of the program indicated an improvement in the quality of students’ Qur’anic recitation in terms of makhārijul huruf (proper articulation of letters), application of tajwid rules, and fluency in reciting the Qur’an in a tartil manner. In addition, students were able to identify and comprehend the Islamic educational values contained in Surah Luqman verses 12–19, such as the values of monotheism (tauhid), gratitude, filial piety, awareness of Allah’s supervision, the obligation to establish prayer, enjoining good and forbidding evil, patience, and social ethics. The integration of tahsin and tadabbur in this program provided a comprehensive and applicable learning experience in shaping the religious character of students as prospective Islamic educators